Selling through Priceline? On the impact of name-your-own-price in competitive market. (4th March 2017) - Huang, Xiao; Sošić, Greys; Kersten, Gregory
ABSTRACT: Priceline.com patented the innovative pricing strategy, Name-Your-Own-Price (NYOP), that sells opaque products through customer-driven pricing. In this article, we study how competitive sellers with substitutable, non-replenishable goods may sell their products (i) as regular goods, through a direct channel at posted prices, and possibly at the same time (ii) as opaque goods, through a third-party channel that engages in NYOP. We establish a stylized model framework that incorporates three sets of stakeholders: two competing sellers, an intermediary NYOP firm, and a sequence of customers. We first characterize customers' optimal purchasing/bidding decisions under various channel structures and then analyze corresponding sellers' dynamic pricing equilibrium. We conduct extensive numerical studies to illustrate the impact of inventory and time on equilibrium prices, expected profit, and channel strategies. We find that the implications are highly dependent on channel structure (dual versus single). In particular, more inventory may reduce one's expected profit under the dual structure, whereas this never happens when a seller only uses the direct channel. Interestingly, although competing sellers seldom benefit from the existence of NYOP channels, it is possible that one or both of the sellers adopt it in equilibrium. We identify timing, inventory levels, and channel opaqueness as key drivers for NYOP adoption and characterize equilibrium areas for each type of channel structure.